Lateral Cephalometric Linear Measurement Standards of Mongolian Children with Normal Occlusion from 6-7 Years of Age - Sainbayar, Bolormaa; Ganburged, Ganjargal; Demid, Odonchimeg; Bazar, Oyuntsetseg; Moriyama, Keiji (Central Asian Journal of Medical Sciences, 2017)
Objectives: The aim of this study was to analyze craniofacial linear dimensions in subjects with normal occlusions to establish age and gender-specific lateral cephalometric linear measurement norms for Mongolian children. Methods: 161 six year old children and 122 seven year old children were recruited for this study. Digital cephalograms of 75 six year old children (34 male and 41female), 49 seven year old children (22 male and 27 female) were selected to establish lateral cephalometric linear measurement norms. Anatomic landmarks were identified directly on the digital images. The means and standard deviations of linear measurements were calculated using 18 variables. Student’s t-test was employed to test for gender differences in each age. Results: Anterior cranial base length and midfacial length were significantly larger in six year old male subjects. Mo-Ms and A-Ptm were significantly larger in seven year old male subjects. Conclusion: Our results showed that linear craniofacial dimension of the hard tissue was gender-dependent. Therefore, gender-specific differences of craniofacial distances should be taken into account during diagnosis and treatment planning. The results from this study can be used as reference values for 6-7 years old children of Mongolia.